Urgensi Reformasi Basis Kekuasaan Birokrasi di Indonesia - Pratikno Pratikno (Magister Administrasi Publik, 1998)
This article tries to address a question of why a strong and dominant bureaucracy, which was an effective and efficient instrument for development at the early stage of the Indonesia's New Order period, start to loose its effective performance in the last few years. The main point discussed here is the inability of the Indonesian bureaucracy to develop legitimacy and support from the society, especially support toward development programs stipulated and controlled by the bureaucracy. In many cases the bureaucracy has to 'buy' and force' society's support which is artificial one. Therefore, it is argued here that the basis of power of Indonesian bureaucracy should be changed from